THE OUTCOMES OF PEDICLED MSAP FLAP FOR PROXIMAL LEG RECONSTRUCTION - Katpar, Hira; Rana Hassan Javaid; Rao Saood Ahmed; Abdul Rasool; Farah Naz; Sara Noor (Journal of Ayub Medical College Abbottabad, 2023)
Background: Reconstruction of defects around the knee and proximal leg are difficult to reconstruct. Out of the multiple flaps described for reconstruction, the pedicled Medial Sural Artery Perforating Flap (MSAP) has recently gained popularity. We conducted this study to assess the clinical outcomes of pedicled MSAP for this purpose at our hospital. Methods: A descriptive case series was conducted from April 2022 to March 2023. All patients above 18 years with defects around the knee and proximal leg were included. Patients with tissue loss in the calf area were excluded. Results: A total of 14 patients were included. Twelve (86%) were males, while only 2 were females (14%). The mean age was 33.5 years (±8.76). The most common cause of the defect was trauma (n=11, 85%). The Mean distance of the distal-most perforator from the popliteal crease was 12.714(±1.990) cm (range 9-16 cm). It was observed that the most distal perforator is usually present in a 2 cm radius of the medial musculo-tendinous junction of the gastrocnemius. Complications were seen in 2 (14%) patients. The mean duration of hospital stay was 4.2(±0.96) days. Patients were followed up weekly for the first two weeks and then at 1, 3 and 6 months. Conclusion: MSAP Flap is a reliable thin, long pedicled fasciocutaneous flap with low donor site morbidity and aesthetically good results for reconstruction around the knee and proximal leg.